Effects of added zinc in diets with ractopamine HCl on growth performance, carcass characteristics, and zinc concentrations in plasma, loin, and liver of finishing pigs - Paulk, Chad B.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S.; Gonzalez, John M.; DeRouchey, Joel M.; Goodband, Robert D.; Hill, G. M.; Haydon, K. D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Two experiments were conducted to determine the effects of added Zn from zinc oxide (ZnO) or Availa-Zn (AZ; Zinpro, Eden Prairie, MN) on growth performance and carcass characteristics of finishing pigs fed ractopamine HCl (RAC; Paylean; Elanco Animal Health, Greenfield, IN). In Exp. 1, a total of 320 pigs (PIC 327 × 1050, initially 215.9 lb) were used in a 35-d study. Pens of pigs were randomly allotted to 1 of 8 dietary treatments, with either 2 barrows or 2 gilts per pen and 20 pens per treatment. Dietary treatments included: a corn-soybean meal–based negative control (0.66% standardized ileal digestible [SID] lysine); a positive control diet (0.92% SID lysine) containing 10 ppm of RAC; and the RAC diet plus 75, 150, or 225 ppm added Zn from ZnO or AZ. The trace mineral premix provided a basal level of 55 ppm Zn from Zn Sulfate (ZnSO4) in all diets. In Exp. 1, overall (d 0 to 35), pigs fed RAC had improved (P < 0.04) ADG, F/G, d-35 BW, caloric efficiency on an ME and NE basis, HCW, carcass ADG and F/G, loin depth, percentage lean, and carcass caloric efficiency on an ME and NE basis, and reduced (P < 0.01) ADFI and backfat thickness compared with pigs fed the control diet. No evidence of a Zn effect or an interaction between Zn source and level was observed. Performance and IOFC did not differ in pigs fed diets with added Zn from either source. In Exp. 2, a total of 1,234 pigs (PIC 337 × 1050; initially 228.6 lb) were used in a 28-d study. Pens contained 23 to 28 pigs with either all barrow, all gilt, or mixed-sex allotments. Pens of pigs were blocked by BW, feeder type, and gender and were randomly assigned to diets. The 4 dietary treatments consisted of (1) a corn-soybean meal–based negative control diet (0.70% SID lysine); (2) a positive control diet (0.92% SID lysine) containing 10 ppm RAC; or the RAC diet plus 50 ppm added Zn from ZnO (3) or AZ (4). All diets contained 80 ppm Zn from ZnO provided by the trace mineral premix. On d 14, the 6 heaviest pigs from each pen (determined visually) were individually tattooed by pen and harvested to allow for carcass data collection, and on d 28, the remaining pigs were individually tattooed by pen and harvested to allow for carcass data collection. Overall (d 0 to 28), pigs fed RAC had improved (P < 0.001) ADG, F/G, final BW, and caloric efficiency on an ME and NE basis. Added Zn or Zn source did not affect (P > 0.20) growth performance. For pigs harvested on d 14, pigs fed RAC had improved (P < 0.001) carcass ADG, F/G, income over feed cost (IOFC), and carcass caloric efficiency on an ME and NE basis and a tendency for increased HCW, loin depth, and percentage lean compared with those fed the negative control diet. No differences were observed in carcass characteristics (P > 0.11) between pigs fed RAC diets and diets containing added Zn; however, pigs fed diets with added Zn from ZnO had increased (P < 0.05) carcass F/G, carcass yield, carcass IOFC, and carcass caloric efficiency on an ME and NE basis compared with those fed Zn from AZ. For pigs harvested on d 28, pigs fed RAC had improved (P < 0.01) HCW, carcass ADG and F/G, backfat thickness, loin depth, percentage lean, carcass IOFC, and carcass caloric efficiency on an ME and NE basis. No differences were observed in carcass characteristics between pigs fed RAC, and no additional Zn and diets containing added Zn from either source. Carcass characteristics did not differ in pigs fed diets with added Zn from ZnO vs. AZ. In conclusion, we observed improvements in growth and carcass performance from adding RAC similar to previous studies. In contrast with our previous research, these data indicate that adding Zn to finishing pig diets containing RAC did not improve overall performance. Consistent with the earlier research, income over feed cost (IOFC) was numerically increased with the addition of Zn.
Keywords: Finishing pig; Ractopamine HCl; Zinc